2018
DOI: 10.1177/0363546517750627
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Clinical Outcomes After Microfracture of the Glenohumeral Joint: Average 10-Year Follow-up

Abstract: Treating full-thickness symptomatic chondral defects of the glenohumeral joint with microfracture can result in long-term improved function and reduced pain for some patients. However, in this case series, 21.4% of patients required conversion to arthroplasty <10 years after the index microfracture procedure, and 33% to 42% of patients were considered to have potential clinical failure. Additional studies with larger patient cohorts are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 38 publications
1
52
0
Order By: Relevance
“…The results of microfracture may be lasting as well. Wang et al 24 found an overall survival rate of 76.6% after microfracture, with an average of 10-year follow-up in 13 patients. The authors also reported statistically significant improvements in VAS, SST, and ASES, without any significant change from the short-term (mean, 2.3 years) to long-term (mean, 10.2 years) follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The results of microfracture may be lasting as well. Wang et al 24 found an overall survival rate of 76.6% after microfracture, with an average of 10-year follow-up in 13 patients. The authors also reported statistically significant improvements in VAS, SST, and ASES, without any significant change from the short-term (mean, 2.3 years) to long-term (mean, 10.2 years) follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, the mean glenoid defect size ranges from 1.12 to 2.73 cm 2 , whereas the mean humeral defect size ranges from 4.22 to 6.00 cm 2 (Table 2). 3,[13][14][15][16] The mean articular cartilage depth of the humerus has been reported to be 1.24 mm, ranging from approximately 1.3 mm centrally and thinning to less than 1 mm along the periphery, and the mean depth of the glenoid fossa has been reported to be 1.88 mm. 17 Regeneration of lost cartilage has been the ultimate goal for treatment of articular cartilage defects of the glenohumeral joint.…”
Section: Discussionmentioning
confidence: 99%
“…1,4 This technique has shown good results for small lesions but may lead to fibrocartilage buildup, with limited efficacy for larger lesions and poor long-term results. 3,13,14,18 In an osteochondral autograft procedure, osteochondral autograft plugs consisting of bone and cartilage are harvested, often from the knee, are then transferred and applied onto the defect. 19,20 However, a common complication is harvest-site morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…9,21,23 Microfracture has been reported to have 33% to 42% poor outcomes at midterm follow-up. 24 Osteochondral allograft has a graft failure rate of 22% at 5 years after surgery. 18…”
Section: Discussionmentioning
confidence: 99%